Establishment of Optogenetic Modulation of cAMP for Analyzing Growth, Biofilm Formation, and Virulence Pathways of Bacteria Using a Light-Gated Cyclase - Manish Singh Kaushik; Swaroop Ranjan Pati; Shivanika Soni; Ayushi Mishra; Kumari Sushmita; Suneel Kateriya (Applied Sciences, 2020)
In bacteria, cyclic adenosine monophosphate (cAMP) signaling plays an essential regulatory role whose modulation via optogenetic tools would provide researchers an immense opportunity to control biological processes simply by illumination. The cAMP signaling in bacteria is a complex network of regulatory pathways, which utilizes distinct proteomic resources under different nutrient environments. We established an optogenetic modulation of cAMP and studied important cellular process of growth, biofilm formation, and virulence in the model bacterium E. coli using a light-gated adenylate cyclase (LgAC) from Beggiatoa sp. Blue light-induced activation of LgAC elevated the cAMP level in a blue light-dependent manner in E. coli. Quantitative proteomics revealed a decrease in the level of certain proteins governing growth (PTS, Adk, AckA, GlnA, and EFP), biofilm formation (IhfA, flagellin, YajQ, YeaG, and HlfC), and virulence (ClpP, YebC, KatE, BtuE, and Zur) in E. coli cells expressing LgAC upon blue light illumination. This optogenetic modulation of cAMP would be useful for deciphering cAMP-associated host–pathogen signaling of bacterial systems. Proteome knowledge established by this research work would also be useful for the scientific community while adapting LgAC-based optogenetic modulation for studying other relevant cAMP-driven bacterial physiology (e.g., energy metabolism). The systematic utilization of the established method and more extensively designed experiments regarding bacterial growth, biofilm, survival, and virulence might provide a road map for the identification of new targets for developing novel antibacterial drugs.